Passive Translation Patterns of Indonesian from Arabic Active Constructions: A Semantic–Pragmatic Analysis: English - Khambali; Siti Masyitoh; Kiki Cahya Muslimah (Al-Fakkaar, 2026)
This study investigates Indonesian passive translation patterns from Arabic active constructions through semantic-pragmatic analysis. The complexity of Arabic naḥwu produces varied uslūb for high accuracy of meaning, often resulting in rigid translations in the qawā'id wa tarjamah method in Indonesia. Online news data (BBC, Aljazeera) revealed seven patterns in which Arabic active verb compositions were translated as Indonesian passives. Arabic's rich grammatical system often employs active verb patterns—such as fi‘il + maf‘ūl bihi (ḍamīr) + fā‘il, tamma/yatimmu + maṣdar variants, and relative clause structures—that yield more idiomatic passive renderings in Indonesian, as confirmed by expert discussions and AI tool consistency checks (Reverso Context, Google Translate, Perplexity, ChatGPT). Seven distinct patterns are identified, emphasizing lexical composition and implicature theory over traditional majhūl/maf‘ūl focus, enabling precise, natural translations for Arabic-Indonesian pedagogy. The findings imply the importance of understanding active-passive translation beyond the traditional majhūl-maf'ūl contrastive material.